Annulment of Marital Property Agreements Due to Vitiating Factors: A Comparative Study Between Indonesian and English Law - Sirait, Priscila; Marsal, Irsyaf (Dinasti Research, 2025)
This article examines how annulment of marital property agreements occurs when consent is tainted by vitiating factors. The research object focuses on prenuptial agreements in Indonesia and financial settlement agreements in England. The objective of this study is to analyze the legal framework, judicial practice, and consequences of annulment caused by error, misrepresentation or fraud, or duress in both jurisdictions. Using normative legal research, this study employs statutory, conceptual, comparative, and case approaches, supported by deductive analysis of legislation, jurisprudence, and scholarly opinion. The results show that under Indonesian law, annulment is possible when an agreement is proven to be based on false or misleading information, as exemplified by Denpasar District Court Decision No. 1308/Pdt.G/2019/PN.Dps, which annulled a prenuptial agreement due to misrepresentation. Meanwhile under English law, annulment is recognized in cases of fraudulent misrepresentation, as highlighted in Sharland v Sharland [2015] UKSC 60, where intentional dishonesty invalidated a financial settlement agreement. The conclusion affirms that such agreements are voidable and although annulment safeguards fairness and genuine consent, the division of marital property must still be pursued through separate judicial proceedings as the consequences in both legal systems.